Sharing Economy as a Contributor to Sustainable Growth. An EU Perspective - Florin Bonciu; Ana-Cristina Bâlgăr (Romanian Journal of European Affairs)
The paper bases its analytical approach on two assumptions: the first refers to a significant change taking place in the contemporary world economy – the phenomenon of multipolarity – and proposes a new concept, that of multi-level manifestation of multipolarity; the second has in view the need of a new model of sustainable economic growth. In the context of these two points of view, the paper analyses the sharing economy as a potential significant contributor to sustainable economic growth. The conclusion of this research is that sharing economy has a huge potential of involving millions or even billions of participants and of capitalizing the existing assets while providing spill over effects in the economy. The authors expect sharing economy to become a form of economic activity that will complement traditional forms of business while generating positive economic, social and environmental effects